Effect of characteristics of chemical combined of graphene oxide-nanosilica nanocomposite fillers on properties of cement-based materials. (20th November 2019) - Hu, Miaomiao; Guo, Jintang; Li, Pengpeng; Chen, Di; Xu, Yang; Feng, Yakai; Yu, Yongjin; Zhang, Hua
Highlights: Nanosilica provides physical barrier to prevent GO from aggregation. GO-NS shows pozzolanic properties. GO-NS ameliorate the interface between GO and cement via formation of C-S-H. Chemical combined GO and NS show synergistic effect in cement composite. Abstract: In this study, graphene oxide-nanosilica (GO-NS) was prepared by the reported sol–gel method, and the concept of nanocomposite was creatively introduced to prevent GO from aggregating. Results showed that the nanosilica particles on GO surface formed a physical barrier to maintain GO and NS disperse well in pore solution, respectively. The reaction in saturated Ca(OH)2 solution was conducted to investigate the pozzolanic effect of GO-NS. When added into cement, GO and NS resulted in a cooperative improvement in the mechanical properties of cement composite, and the enhancing mechanisms were investigated by X-ray diffraction (XRD), Raman and SEM. It revealed that GO-NS with refined surface could provide more nucleation sites during hydration and decrease the orientation index of CH crystal. Moreover, some calcium hydroxide (CH) transformed into calcium silicate hydrate (C-S-H) due to the pozzolanic NS coating. The layered nanocomposites provided platforms for the deposition and growth of C-S-H.